An Ileo-ceco-colo-colic Intussusception in a 12-Year-Old Female: A Case Report and Review of the Literature - Vaghela, Parth; Damor, Maya (Lietuvos chirurgija, 2025)
Introduction. Intussusception is a leading cause of acute intestinal obstruction in young children, most commonly occurring between 6 months and 2 years of age. However, it becomes increasingly rare in older pediatric populations and often presents with atypical features. Among the uncommon variants, ileo-ceco-colo-colic intussusception – where the terminal ileum, cecum, and segments of the colon invaginate into the distal colon – represents an extremely rare and complex entity. Prompt recognition and timely intervention are essential to prevent complications such as bowel ischemia and necrosis. Case presentation. We present the case of a 12-year-old previously healthy female who arrived at the emergency department with acute onset abdominal pain, bilious vomiting, and rectal bleeding. Abdominal ultrasound and contrast-enhanced CT scan revealed a long-segment intussusception involving the terminal ileum, cecum, ascending colon, and extending into the transverse colon. Attempts at non-operative (pneumatic) reduction were unsuccessful. Due to clinical signs of peritonism and suspected bowel ischemia, an emergency exploratory laparotomy was performed. Intraoperative findings confirmed a non-reducible intussusception with segments of non-viable bowel. A right hemicolectomy with primary ileocolic anastomosis was carried out. Histopathological analysis demonstrated hypertrophied Peyer’s patches as a possible lead point, without evidence of malignancy or other pathological lesions. Conclusions. This case illustrates a rare and advanced form of intussusception in an older pediatric patient. Given its atypical presentation and increased likelihood of underlying pathology, older children with suspected intussusception warrant thorough evaluation and early surgical consideration. This report emphasizes the importance of maintaining a high index of suspicion, utilizing appropriate imaging modalities, and pursuing timely surgical management when non-operative reduction fails or complications arise.